2022
DOI: 10.5194/acp-2021-1000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light Absorption by Brown Carbon over the South-East Atlantic Ocean

Abstract: Abstract. Biomass burning emissions often contain brown carbon (BrC), which represents a large family of light-absorbing organics that is chemically complex and therefore difficult to estimate their absorption of incoming solar radiation, resulting in large uncertainties in the estimation of the global direct radiative effect of aerosols. Here we investigate the contribution of BrC to the total light absorption of biomass burning aerosols over the South-East Atlantic Ocean with different optical models utilizi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…Following Carter et al (2021), we also evaluate the MAC relative to the BC+OA mass concentration at a λ of 470 nm. At λ=660 nm, the solar absorption will be dominated by the black carbon, whereas at λ=470 nm the MAC BC+OA will contain contributions from both OA-induced brown carbon as well as other wavelength-dependent absorbers (Zhang et al, 2022). -S8).…”
Section: Optical Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Carter et al (2021), we also evaluate the MAC relative to the BC+OA mass concentration at a λ of 470 nm. At λ=660 nm, the solar absorption will be dominated by the black carbon, whereas at λ=470 nm the MAC BC+OA will contain contributions from both OA-induced brown carbon as well as other wavelength-dependent absorbers (Zhang et al, 2022). -S8).…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Taylor et al ( 2020) place an upper estimate of 11% on shortwave absorption by brown carbon (BrC) at 405 nm wavelength by the time the BBA plume reaches Ascension Island, with . Zhang et al (2022) indicate that other non-BrC materials absorb sunlight over the southeast Atlantic as a function of wavelength, so that BrC may contribute even less than < 10% of the total.…”
Section: Is There Evidence Of Brown Carbon?mentioning
confidence: 99%
See 1 more Smart Citation
“…2 shows the evaluated contribution from BrC on total absorption at 464 nm is generally around 1-2%, suggesting BrC have a minimal influence on the ASI. Zhang et al (2022) found around ~10 % of BrC at 470 nm near the African continent, while Taylor et al (2020) found ~10 % BrC at a much lower wavelength (405 nm) in the free troposphere near Ascension Island. In contrast to these measurements in the free 220 troposphere, our observed BB plumes are generally considered to have experienced cloud processing, which could further reduce the BrC content (Che et al, 2022a).…”
Section: Monthly Variation Of Optical Properties Of Bb Aerosols 180mentioning
confidence: 98%
“…This method is similar to the one used by Taylor et al (2020), while it may bring uncertainties as the AAE of BC is not always , 2013;Zhang et al, 2022). Note that most of the BC observation for September and October 2017 is unreliable due to issues with the inlet system.…”
mentioning
confidence: 99%